Privacy protection of warning message publishing protocol in VANET - Hui LIU; Xinyan LIU; Yan XU; Hong ZHONG; Meng WANG (Tongxin xuebao)
Aiming at the problem that the traffic control department publishes violation messages to vehicles, a privacy protection warning message publishing protocol was proposed, where transportation manage department could obtain vehicle’s pseudonym according to its real identity and send warning message to vehicles based on its pseudonym in VANET.Elliptic curve cryptography was used to construct a lightweight warning message publishing and receiving process.Furthermore, the conditional privacy protection was realized, which could effectively protect the identity privacy of the receiving vehicle.Security analysis shows that the proposed protocol can meet the security requirements of VANET.Performance analysis shows that the protocol protocol has lower computational overhead and communication overhead.